Chromosomal polymorphism of Belgica antarctica populations: possible links on ecology and geography - Kovalenko, Pavlo (Ukrainian Antarctic Journal, 2024)
Chromosomal inversion polymorphism is an important evolutionary mechanism for many species, particularly insects. Belgica antarctica (Chironomidae) is the only endemic insect of the Antarctic Peninsula and is currently considered a model organism for studying adaptations of living organisms to climate change in the extreme terrestrial ecosystems of Antarctica. This polar midge has salivary gland polytene chromosomes, making it convenient for investigating various chromosomal aberrations and analysing their potential relationship with geographical and ecological factors. In this study, chromosomal polymorphism was analysed in the salivary glands of 99 fourth-instar larvae of Belgica antarctica, collected in four different localities in the West Antarctic Peninsula region in 2022. Six of the seven previously described heritable heterozygous inversions for this species were found in the newly tested populations. Notably, the precise location of a large inversion in chromosome I, containing the nucleolar organizer region, was identified for the first time since its discovery in 1962. Additionally, the data on chromosomal inversion frequencies were combined with all currently available data – together from 1436 Belgica antarctica individuals across 26 populations, from 1962 to 2022, to determine potential links to specific ecological (ecological complexity, ornithogenic influence, and whether samples were collected from nesting or non-nesting material) and geographical (longitude and latitude) factors. It was found that, overall, the ecological factors do not affect the frequency of the studied inversions. However, slight trends were observed in the frequency of four heterozygous rearrangements with latitude, as well as the frequency of specimens with at least one non-sex-linked heterozygous inversion with longitude.